2011
DOI: 10.1007/978-3-642-25734-6_127
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Performance Analysis of MANET Routing Protocols Using NS2 Simulator

Abstract: Abstract. In the routing strategic approach, mostly in wireless scenario, primary emphasis is given on path routing and routing protocol selection. Again in Mobile Ad hoc Network (MANET) a routing protocol is to be selected in such a way that the network can be suitably designed to give best data delivery as well data integrity. So performance analysis of the protocols is the major step to select these protocols. In this paper comparative performance analysis like delay, throughput, control overhead, and PDR i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…If after this search, there is no route, then this is marked as unreachable or unrecoverable. 7 In our case NET TRAVERSAL TIME = 2 x NODE TRAVERSAL TIME x NET DIAMETER = 2 x (40 ms) x 5 = 400 ms = 0.4 s 8 The waiting time for the RREP corresponding to the second RREQ is 2 x NET TRA-VERSAL TIME milliseconds = 0.8 s.…”
Section: Route Establishment and Recoverymentioning
confidence: 73%
See 1 more Smart Citation
“…If after this search, there is no route, then this is marked as unreachable or unrecoverable. 7 In our case NET TRAVERSAL TIME = 2 x NODE TRAVERSAL TIME x NET DIAMETER = 2 x (40 ms) x 5 = 400 ms = 0.4 s 8 The waiting time for the RREP corresponding to the second RREQ is 2 x NET TRA-VERSAL TIME milliseconds = 0.8 s.…”
Section: Route Establishment and Recoverymentioning
confidence: 73%
“…Many studies on MANETs have been based on simulation. The most popular simulation tools for ad hoc networks are OPNET, see an example in [5,6], ns-2 [7], and Glomosim, see [8]. However, these are not the only tools available to study this type of network.…”
Section: Introductionmentioning
confidence: 99%
“…S. Mohapatra et al [19], in their subsequent publication, performed a comparative assessment of AODV, DSDV, and OLSR routing protocol using NS-2. They have analyzed-throughput, packet delivery ratio & control overhead and concluded that the OLSR gives better packet delivery fraction.…”
Section: Related Workmentioning
confidence: 99%
“…In 2011, Mohapatra et al [30] studied the effect of change in network size, mobility and pause time on AODV, OLSR and DSDV. The number of nodes was fixed at 30.…”
Section: State Of the Artmentioning
confidence: 99%